Positive and negative intronic regulatory elements control muscle-specific alternative exon splicing of Drosophila myosin heavy chain transcripts. - Standiford, D M (2001)
Alternative splicing of Drosophila muscle myosin heavy chain (MHC) transcripts is precisely regulated to ensure the expression of specific MHC isoforms required for the distinctive contractile activities of physiologically specialized muscles. We have used transgenic expression analysis in combination with mutagenesis to identify cis-regulatory sequences that are required for muscle-specific splicing of exon 11, which is encoded by five alternative exons that produce alternative "converter" domains in the MHC head. Here, we report the identification of three conserved intronic elements (CIE1, -2, and -3) that control splicing of exon 11e in the indirect flight muscle (IFM). Each of these CIE elements has a distinct function: CIE1 acts as a splice repressor, while CIE2 and CIE3 behave as splice enhancers. These CIE elements function in combination with a nonconsensus splice donor to direct IFM-specific splicing of exon 11e. An additional cis-regulatory element that is essential in coordinating the muscle-specific splicing of other alternative exon 11s is identified. Therefore, multiple interacting intronic and splice donor elements establish the muscle-specific splicing of alternative exon 11s.